2007
DOI: 10.1016/j.trstmh.2006.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant hepatic failure in northern Brazil: morphological, immunohistochemical and pathogenic aspects of Lábrea hepatitis and yellow fever

Abstract: A morphological evaluation of histopathological liver samples from 42 fulminant hepatic failure cases from the Amazon Basin was undertaken in order to differentiate yellow fever (YF) from Lábrea hepatitis (LH) and other entities. The pattern and distribution of liver cell death as well as ballooning degeneration and midzonal apoptotic bodies were the most distinctive features of YF, whereas morula cells were the major finding for LH. Nineteen well characterised cases were further submitted to immunohistochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
1
13
0
2
Order By: Relevance
“…Usually, this involves little to no immune cell infiltration of the liver (Bernal et al 2015, Yoon et al 2016). In this study, we found that ballooning degeneration of hepatocytes (a well-established indicator of hepatic necrosis) (Dias et al 2007) was significantly increased, following simultaneous acetaminophen overdose and T. crassiceps infection. Interestingly, levels of serum ALT were higher in parasitised mice that received acetaminophen than in non-parasitised mice that received acetaminophen.…”
Section: Discussionmentioning
confidence: 72%
“…Usually, this involves little to no immune cell infiltration of the liver (Bernal et al 2015, Yoon et al 2016). In this study, we found that ballooning degeneration of hepatocytes (a well-established indicator of hepatic necrosis) (Dias et al 2007) was significantly increased, following simultaneous acetaminophen overdose and T. crassiceps infection. Interestingly, levels of serum ALT were higher in parasitised mice that received acetaminophen than in non-parasitised mice that received acetaminophen.…”
Section: Discussionmentioning
confidence: 72%
“…The main histopathological changes are described in Table 1. Among the histological characteristics present in YFVinfected humans, hepatocellular balloonism, Councilman corpuscle and the presence of apoptotic acidophilic bodies are the most evident findings in these patients [14,20,21] . The approach of the histological alterations of YFV and DENV is of great importance for the differential diagnosis, mainly because both diseases cause clinical manifestations of similar acute phase, but the hepatic damages in YFV infections are more serious and with a higher mortality rate when compared to DENV [20] .…”
Section: Histopathological Alterations Found In the Liver After Infecmentioning
confidence: 97%
“…The approach of the histological alterations of YFV and DENV is of great importance for the differential diagnosis, mainly because both diseases cause clinical manifestations of similar acute phase, but the hepatic damages in YFV infections are more serious and with a higher mortality rate when compared to DENV [20] . Diagnosis based on the YFV morphological changes is currently the gold standard for identifying the infection, based on specific morphological characteristics of liver damage, as mentioned previously, and which are observed in almost all human cases [14,22] . It is worth mentioning that the severity of hepatic changes is associated with circulating virus strain and host susceptibility [23] .…”
Section: Histopathological Alterations Found In the Liver After Infecmentioning
confidence: 99%
See 2 more Smart Citations